As passagens do sagrado: da mercadoria ao ex-voto no Santuário Nacional de Nossa Senhora Aparecida/Brasil - Souza, Bianca Gonçalves de [UNESP]; Marañon, Eduardo Murguia [UNESP] (OpenEdition, 2013)
This article reflects on the votive objects exhibited in the room of promises situated in the National Sanctuary of Nossa Senhora da Conceição Aparecida, located in the city named Aparecida (São Paulo, Brazil). At the sanctuary, there is an area to receive and exhibit votive offerings, which are donated as payment or to initiate a relationship of faith. This article’s aim is to understand how, from entering the room of promises, the votive object is selected and receives new directions, within the Sanctuary or outside it. Nonetheless, a small number are kept in this specific room dedicated to votive offerings. These objects become documents, social agents, because they reveal stabilization within associative relationships. With the help of readings from Information Science and other areas, and after carrying out ethnographic research over three years, this article shows how the materiality of information is indispensable for apprehending the relationship between society and information. Through contact with the votive offerings, the visitor establishes inferences, interpretations, which assist in comprehending the space, faith, and Nossa Senhora da Conceição Aparecida.

O presente artigo reflete sobre os objetos votivos expostos na sala das promessas situada no Santuário Nacional de Nossa Senhora da Conceição Aparecida, localizado no município de Aparecida (S. Paulo, Brasil). Nesse local, há um espaço para recebimento e exposição dos ex-votos objetos, doados como paga de promessa ou para iniciarem uma relação de fé. O objetivo do artigo é compreender como, desde o ingresso na sala das promessas, o objeto votivo é selecionado e a ele dado novos rumos, no interior do Santuário ou para fora dele. No entanto, uma pequena quantidade permanece no interior da sala das promessas. Esses objetos tornam-se documentos, agentes sociais, pois revelam estabilizações no interior das relações associativas. Com o auxílio de leituras provindas da Ciência da Informação e de outras áreas, e após pesquisa de campo efetuada no local nos últimos três anos, o artigo demonstra como a materialidade da informação é imprescindível para se apreender a relação da sociedade com essa. No contato com o ex-voto, o visitante estabelece inferências, interpretações, que o auxiliam na compreensão do espaço, da fé, da figura de Nossa Senhora da Conceição Aparecida.